THE ISLAMIC RELIGIOUS EDUCATION TEACHERS' STRATEGIES TO IMPROVE THE LEARNING MOTIVATION OF THE ALPHA GENERATION THROUGH INFORMATION TECHNOLOGY-BASED LEARNING - Salim, Wilda Fauziah (Pergunu Jawa Barat, 2025)
Generation Alpha, the generation born around 2010 until today, is of particular concern in education, especially at the primary school level. They are known to be very familiar with technology from an early age, because they have been accustomed to using digital devices such as gadgets and smartphones. This condition requires the world of education, especially Islamic Religious Education (PAI), to adjust its learning approach to be relevant to the characteristics of this generation. This study uses a qualitative method, as explained by Nana Syaodih Sukmadinata that qualitative research aims to describe and analyse social phenomena, attitudes, and thoughts of individuals or groups inductively, by letting problems emerge from the data naturally. The results showed that PAI and Budi Pekerti teachers at SD Negeri Wadas I, Telukjambe Timur Subdistrict, have tried to increase Alpha generation's learning motivation through information technology-based learning. The role of the teacher is not only as a teacher, but also as a facilitator and innovator in developing professionalism that is relevant to the times. This role is realised through the preparation of training, coaching and guidance programmes related to the use of technology in learning. The competence of technology-based teachers includes four main aspects, namely understanding of technology (digital literacy), the ability to apply technology in learning, ino.